2018
DOI: 10.1097/j.pain.0000000000001386
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol modulates serotonergic transmission and reverses both allodynia and anxiety-like behavior in a model of neuropathic pain

Abstract: Clinical studies indicate that cannabidiol (CBD), the primary nonaddictive component of cannabis that interacts with the serotonin (5-HT)1A receptor, may possess analgesic and anxiolytic effects. However, its effects on 5-HT neuronal activity, as well as its impact on models of neuropathic pain are unknown. First, using in vivo single-unit extracellular recordings in rats, we demonstrated that acute intravenous (i.v.) increasing doses of CBD (0.1-1.0 mg/kg) decreased the firing rate of 5-HT neurons in the dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
213
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(227 citation statements)
references
References 89 publications
6
213
1
7
Order By: Relevance
“…Its efficacy with migraines and mood disorders has been consistently noted in the literature as well [17][18][19]. A recent preclinical study demonstrated effective neuropathic pain and comorbid anxiety and depression reduction through its interaction with the serotonin 5-HT 1A receptor [20]. It is speculated that this might be the physiological model responsible for the noted improvement in the case study.…”
Section: Discussionmentioning
confidence: 61%
“…Its efficacy with migraines and mood disorders has been consistently noted in the literature as well [17][18][19]. A recent preclinical study demonstrated effective neuropathic pain and comorbid anxiety and depression reduction through its interaction with the serotonin 5-HT 1A receptor [20]. It is speculated that this might be the physiological model responsible for the noted improvement in the case study.…”
Section: Discussionmentioning
confidence: 61%
“…The participation of the 5-HT system in similar behaviors across the animal kingdom suggests that its function is conserved in most animal phyla. It can be also observed in functions that have not been covered in this review such as pain [213][214][215][216]. Moreover, in several behavioral responses, several 5-HTRs can be involved implying tight 5-HT regulatory mechanisms in responses to various stimuli.…”
Section: Discussionmentioning
confidence: 87%
“…This is consistent with reports of anxiolytic effects of CBD in a chronic unpredicted stress model in mice using both elevated plus maze and novelty supressed feeding test (Campos et al, ; Campos & Guimarães, ; Fogaca, Campos, Coelho, Duman, & Guimaraes, ) where an action of CBD to inhibit TRPV1, CB 1 and CB 2 was implicated respectively. Anxiolytic effects of CBD have also been observed in a mouse model of neuropathic pain where inhibition of 5‐HT 1A receptors was implicated (De Gregorio et al, ).…”
Section: Discussionmentioning
confidence: 99%